Applicability of the SERVQUAL instrument under South African conditions : an assessment of four situations - Pitt, Leyland Frederick (Rhodes University, Faculty of Commerce, Department of Management, 1992)
On-going research in recent years has shown quality of product and service, as perceived by customer, relative to competition, to be the single most important factor contributing to organizational well-being. Quality of product and service also presents one of the most significant opportunities for corporate differentiation. A major requirement for the successful management of quality is therefore effective measurement. In the case of physical goods, progress has been made over a long period. However, in the case of services, real advances have only occurred within the past decade. The importance of service quality is also highlighted by the fact that most businesses today are losing customers due to its inadequacy, rather than poor products. Indeed, from the customer's point of view, services and products probably do not exist in a dichotomy, but, rather, along a spectrum. Therefore, the measurement of service quality is critical, not only in traditional service organizations, but in manufacturing situations as well. The development of the SERVQUAL questionnaire in 1988, offered researchers, perhaps for the first time, an apparently reliable and valid instrument for the measurement of service quality. However, to date the instrument has not been subjected to rigorous testing for reliability and validity in South Africa, across a range of service organizations, within a typology. In this study, the SERVQUAL instrument was used to measure service quality across a range of firms within the Larsson-Bowen contingency framework, under South African conditions. Its main objectives were to assess its reliability and validity in these circumstances. It was found that SERVQUAL performed well across all organizations within the Larsson-Bowen framework, under South African conditions, with regard to reliability, convergent and nomological validity. Its construct validity proved to be less sound, and it was not found to possess discriminant validity. It is suggested that this is less attributable to South African circumstances than to the nature of the organizations. In cases of low diversity of demand, the instrument appears to capture the essence of service quality less effectively. Means of overcoming this in future studies are suggested, as well as other directions for research in the area of service quality measurement
Keywords: SERVQUAL instrument; Customer service; Measurement; Service quality; South Africa